“Anak adalah Aset”: Meta Sintesis Nilai Anak pada Suku Lani dan Suku Aceh - Agung Dwi Laksono; Ratna Dwi Wulandari (Puslitbang Upaya Kesehatan Masyarakat, 2019)
Abstract Background: If a child gives values that were considered positive or beneficial to parents, then parents will place high expectations on the child. The study was conducted to synthesize the value of children in the Aceh Tribe and the Lani Tribe. Objective: The research aim was to explore the value of children in the Lani and the Acehnese. Methods: Using the meta-synthesis method in two manuscripts resulting from health ethnographic research, namely